Student's E-Planner / Noorizatul Ikhsan Malaki - Noorizatul Ikhsan, Malaki (2003)
Student's E-Planner is web-based planner, targeted for students in University of Malaya. The main agenda is to provide these students an electronic planner that they can access whenever they want and wherever they are, as long as there is an Internet connection. Additionally this planner helps the students to be more organized in managing their daily tasks in a systematic way. This project consists of 2 main modules, which are the administrator module and the student module. The administrator module does all the control and management of the planner and the student module use the system. The system is expected to make students life more easier to organize and manage while at the same time keep track of their busy schedule.